The concept of law - Hart, H. L. A., (Herbert Lionel Adolphus), 1907-1992 (Oxford, United Kingdom : Oxford University Press, 2012)
"Fifty years on from its original publication, HLA Hart's The Concept of Law is widely recognized as the most important work of legal philosophy published in the twentieth century. It is a classic book in the field of legal scholarship and remains the starting point for most students coming to the subject for the first time. Known as Hart's most famous work, The Concept of Law emerged from a set of lectures that Hart began to deliver in 1952 in which he developed a sophisticated view of legal positivism. Hart revolutionized the methods of jurisprudence and the philosophy of law in the English-speaking world by bringing the tools of analytic, and especially linguistic, philosophy to bear on the central problems of legal theory. In this third edition, Leslie Green provides a new introduction that sets the book in the context of subsequent developments in social and political philosophy, clarifying misunderstandings of Hart's project and highlighting central tensions and problems in the work. The Concept of Law remains a must-read for anyone interested in the great thinkers of the 20th century."--Publisher's website.
Persistent questions -- Laws, commands, and orders -- The variety of laws -- Sovereign and subject -- Law as the union of primary and secondary rules -- The foundations of a legal system -- Formalism and rule-scepticism -- Justice and morality -- Laws and morals -- International law.
Includes bibliographical references (pages 277-325) and index.
Self-Renewing
Keywords: Jurisprudence; Law (Philosophical concept); Law -- Philosophy; Jurisprudence -- Methodology